Connecting Resource Tracking by Frugivores to Temporal Variation in Seed Dispersal Networks - Gleditsch, Jason M.; Hruska, Amy M.; Foster, Jeffrey T. (Frontiers in Ecology and Evolution, 2017)
Mutualistic interactions between species are crucial for the maintenance and functioning of the community. Current research has shown the importance of not only understanding the structure of these mutualistic interaction networks but also their temporal dynamics. Temporal changes in species abundance, such as those caused by vertebrate resource tracking, may create temporal variability in a network though neighborhood effects and influence the directedness of dispersal. While much research has been done on resource tracking, neighborhood effects, and directed dispersal individually, little research has been done into their interrelationships and, therefore, theory of how resource tracking can influence frugivory and seed dispersal networks remains poorly developed. We use the available literature to show the prevalence of resource tracking by vertebrate frugivores and hypothesize how, through neighborhood effects, resource tracking may influence short-term variation in network properties. We then discuss how resource tracking can influence long-term network properties by altering the dispersal of plant species. Lastly, we use this information to hypothesize how the introductions of new species into a community may alter the influence of resource tracking on frugivory and seed dispersal. While trait matching and links that are not possible between species in a community (i.e., forbidden links) play a large role in determining the structure of a network, temporal change in the abundance of species due to resource tracking may also affect the properties of networks. By increasing our understanding of the role resource tracking has in the temporal variability of frugivory and seed dispersal networks, we can better determine the full extent of species interactions and provide valuable information for the conservation of ecological communities.